High-loose flake silver powder and preparation method thereof

By controlling the reaction conditions and treatment steps under stirring, a sheet-like silver powder with high loose density was prepared, which solved the problem of poor conductivity and density of the sheet-like silver powder in the prior art, and achieved efficient and low-cost preparation effect .

CN119489199AActive Publication Date: 2025-02-21NINGXIA CNMC NEW MATERIAL CO LTD
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202411576701.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-21
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

The prior art is difficult to prepare sheet silver powder with high loose density, resulting in poor conductivity, density, reliability and printing properties, and high production costs.

Method used

By adding a specific concentration of compound dispersant, silver ammonia solution and compound reducing agent solution in a stirring state, the reaction temperature and time are controlled to form a large number of crystal nuclei, followed by water washing, surface coating and spheroidization treatment, and finally by grinding A sheet-like silver powder with high pine density was obtained.

Benefits of technology

The preparation of sheet silver powder with high loose density is achieved, which improves its conductivity, density, reliability and printing performance, while reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119489199A_ABST
    Figure CN119489199A_ABST
Patent Text Reader

Abstract

The invention discloses high-loose flake silver powder and a preparation method thereof, and belongs to the technical field of conductive materials.The preparation method comprises the steps that in the stirring state, a compound dispersing agent solution is added into a reaction container, then a silver-ammonia solution is added at the flow speed of 1.47-1.96 L / min, a compound reducing agent solution is added at the same flow speed, and then the silver-ammonia solution and the compound reducing agent solution are mixed at the same flow speed; the remaining silver-ammonia solution and the compound reducing agent solution are added into the reactor, the temperature is increased, a reaction is conducted, and spherical silver powder is obtained; washing the spherical silver powder with water until the conductivity is less than or equal to 20 [mu] s / cm, and coating the surface of the washed spherical silver powder with saturated fatty acid; the spherical silver powder with the coated surface is dried and then spheroidized; and after the spheroidized spherical silver powder, unsaturated fatty acid and alcohol are stirred, a grinding ball is added for grinding, and filtering, washing and drying are conducted. The flake silver powder disclosed by the invention is high in apparent density, high in conductivity, good in filling property, excellent in printing performance and low in production cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of conductive materials, and in particular relates to a high-loose flaky silver powder and a preparation method thereof. Background Art

[0002] As a material with better conductivity, flaky silver powder has line contact and surface contact rather than point contact compared to spherical silver powder. This makes the contact resistance of silver powder lower and its conductivity stronger. Therefore, it is widely used in electronic paste industries such as membrane switches, heterojunctions, and conductive adhesives.

[0003] Silver powder is a material with good conductivity. Its conductivity is usually line contact and surface contact. Its contact resistance is low and its conductivity is high. Flake silver powder is widely used in electronic paste industries such as membrane switches, heterojunctions, and conductive adhesives.

[0004] There are two main methods for preparing flaky silver powder: chemical method and physical method. The flaky silver powder prepared by chemical method has great difficulty in process control, poor stability, and whether the later flaking degree can be used in products needs further research, so it is limited to experimental research. The main reason behind this is that the silver powder is too thin, shrinks after sintering, resulting in increased resistance, and has no great use value. The physical ball milling method focuses on high flatness, good stability, and is conducive to industrial production. As an important component of conductive silver paste, the physical properties of flaky silver powder directly determine whether the paste has good conductivity, density, reliability and printability. Flake silver powder with high bulk density is more helpful to improve the conductivity, density, reliability and printability of conductive silver paste. Therefore, the bulk density of flaky silver powder plays an important role in improving the electrical properties of conductive silver paste.

[0005] At present, high bulk density silver powder is mainly concentrated in spherical silver powder, and its bulk density can reach 3.0-4.0g / cm 3 However, due to the influence of the degree of flake formation and the preparation process, the bulk density of flaky silver powder is low, almost maintained at 0.5-1.6 g / cm 3 About. For example, the national patent with publication number CN118023512A discloses a method for preparing low-loose flaky silver powder, which mainly achieves the purpose of low looseness by mixing zirconium oxide balls of different particle sizes and adopting wet grinding. The national patent with publication number CN110026564A discloses a method for preparing low-loose flaky silver powder, which prepares spherical silver powder by chemical method and then grinds low-loose flaky silver powder by wet grinding rod mill. The bulk density of the flaky silver powder prepared in the above two patent documents is only maintained at 0.6-0.8g / cm 3The reason is that in the process of grinding flaky silver powder, as the degree of flake increases, the bulk density is constantly reduced, which also creates a lower bulk density. In other words, it is difficult to obtain high bulk density flaky silver powder to a large extent, but high bulk density has better conductivity, filling, printability and lower cost than low bulk density flaky silver powder. Summary of the invention

[0006] One of the purposes of the present invention is to provide a method for preparing high bulk flaky silver powder, wherein the flaky silver powder prepared by the method has high bulk density, high conductivity, good filling property, excellent printing performance and low production cost.

[0007] A second object of the present invention is to provide a high-volume flaky silver powder.

[0008] In order to achieve one of the above purposes, the present invention adopts the following technical solution:

[0009] A method for preparing high-loose flaky silver powder, characterized in that the preparation method comprises:

[0010] Step S1, under stirring, adding a composite dispersant solution with a mass concentration of 15-25g / L to a reaction container, then adding a silver ammonia solution with a molar concentration of 1-2mol / L at a flow rate of 1.47-1.96L / min, and then adding a composite reducing agent solution with a molar concentration of 0.5-1.5mol / L at the same flow rate, and then adding the remaining silver ammonia solution and the composite reducing agent solution to the reactor at the same flow rate, heating to 45-50°C, reacting for 10-30min, and obtaining spherical silver powder of 1.6-2.5 microns;

[0011] In step S1, the volume ratio of the silver ammonia solution to the composite reducing agent solution is 1:1;

[0012] In the step S1, the mass ratio of the compound dispersant in the compound dispersant solution to the silver nitrate in the silver ammonia solution is 1:6.8-23;

[0013] Step S2, washing the spherical silver powder with water until the conductivity is ≦20 μs / cm, and then coating the surface of the washed spherical silver powder with saturated fatty acid;

[0014] In the step S2, the mass ratio of the saturated fatty acid to the spherical silver powder is 0.002-0.008:1;

[0015] Step S3, drying the surface-coated spherical silver powder and spheroidizing for 3 to 8 minutes;

[0016] Step S4, stirring the spherical silver powder, unsaturated fatty acid grinding aid and alcohol for 8 to 12 minutes, adding grinding balls, grinding for 12 to 18 hours, filtering, washing and drying to obtain high loose flaky silver powder.

[0017] In the step S4, the mass ratio of the unsaturated fatty acid grinding aid, grinding balls, alcohol and spherical silver powder after spheroidization is 0.8-1.0:4.5-5.0:0.6-0.8:1.

[0018] Furthermore, in step S1, the volume ratio of the silver ammonia solution added first to the silver ammonia solution added later is 1:15-20;

[0019] The volume ratio of the composite reducing agent solution added first to the composite reducing agent solution added later is 1:15-20.

[0020] Further, in the step S1, the solute in the composite reducing agent solution is a mixture of ascorbic acid and formaldehyde with a concentration of 37%;

[0021] In the step S1, the compound dispersant is a mixture of polyvinyl pyrrolidone K30 and gum arabic, or a mixture of polyvinyl pyrrolidone K30 and gelatin.

[0022] Furthermore, the mass ratio of ascorbic acid to formaldehyde is 1:1-2;

[0023] The mass ratio of polyvinyl pyrrolidone K30 to gum arabic is 3.5-4.5:1;

[0024] The mass ratio of the polyvinyl pyrrolidone K30 to gelatin is 3.5-4.5:1.

[0025] Furthermore, in the step S1, the stirring speed in the stirring state is 250-350 r / min.

[0026] Furthermore, in the step S2, the electrical conductivity is 15-18 μs / cm.

[0027] Furthermore, in step S2, the saturated fatty acid is one of hexadecanoic acid, stearic acid, lauric acid and myristic acid.

[0028] Further, in the step S4, the diameter of the grinding ball is 1.2 to 1.6 mm;

[0029] The grinding balls are steel balls or zirconium balls.

[0030] Furthermore, in step S4, the unsaturated fatty acid grinding aid is one of oleic acid, linolenic acid, linoleic acid, arachidonic acid and docosenoic acid.

[0031] The electrical conductivity in the present invention may preferably be 15 to 18 μs / cm.

[0032] In order to achieve the second objective above, the present invention adopts the following technical solution:

[0033] A high-pile flaky silver powder is prepared by the method described above.

[0034] In summary, the technical solution of the present invention has the following technical effects:

[0035] The invention ensures that a large number of crystal nuclei are generated first by adding a part of silver ammonia solution and a part of compound reducing agent solution to a compound dispersant solution at the same flow rate, which is beneficial to the growth of silver powder in the later stage; then, the remaining silver ammonia solution and the compound reducing agent solution are added at the same flow rate, which improves the dispersibility of the silver ammonia solution and the compound reducing agent solution, and ensures the full reaction of the silver ammonia solution and the compound reducing agent solution; the particle size of the spherical silver powder is increased by the compound reducing agent solution, which is beneficial to obtain the spherical silver powder with high bulk density; the reaction temperature of the silver ammonia solution and the compound reducing agent solution is controlled at 45-50 DEG C, which ensures that a large number of crystal nuclei are formed in a short time, which is beneficial to the slow growth of the silver powder in the later stage; saturated fatty acid is used for surface coating, and the hydrophilic group carboxyl group and the hydrophobic group CH 2 The long chain makes the silver powder both hydrophilic and hydrophobic, thereby improving the dispersibility of the spherical silver powder, which is beneficial to improving the high bulk density of the flaky silver powder; by compounding the dispersant and spheroidizing, the tap density and bulk density of the spherical silver powder are improved, which is beneficial to obtaining flaky silver powder with high bulk density; the use of unsaturated fatty acids for grinding not only ensures that the unsaturated fatty acids and the substances (saturated fatty acids) coated on the surface of the silver powder are not repelled, but also utilizes the fact that the carbon-carbon double bonds of the unsaturated fatty acids will not rotate, which to a certain extent hinders the stacking and agglomeration of the silver powder, thereby improving the dispersibility of the flake powder and further improving the bulk density of the flaky silver powder; the flaky silver powder of the present invention has a high bulk density, high conductivity, good filling property, excellent printing performance, and low production cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0037] Figure 1 This is a photo of the appearance of the spherical silver powder of Example 1;

[0038] Figure 2 This is a photo of the appearance of the flaky silver powder of Example 1;

[0039] Figure 3 This is a photo of the appearance of the spherical silver powder of Example 2;

[0040] Figure 4 This is a photo of the appearance of the flaky silver powder of Example 2. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0042] Embodiment 1:

[0043] 1. Use silver nitrate to prepare a silver ammonia solution with a molar concentration of 2 mol / L.

[0044] Ascorbic acid and formaldehyde with a concentration of 37% were mixed in a mass ratio of 1:1 to prepare a composite reducing agent solution with a molar concentration of 1 mol / L.

[0045] Polyvinyl pyrrolidone K30 and gum arabic were mixed in a mass ratio of 4:1 to prepare a composite dispersant solution with a mass concentration of 15 g / L.

[0046] The volume ratio of the prepared silver ammonia solution to the compound reducing agent solution is 1: 1. The mass ratio of polyvinyl pyrrolidone K30 and gum arabic in the prepared compound dispersant solution to silver nitrate in the silver ammonia solution is 1:23.

[0047] 2. Under stirring at a speed of 300 r / min, first add the prepared compound dispersant solution into the reaction vessel, then add 1 / 15 of the silver ammonia solution at a flow rate of 1.47 L / min, then add 1 / 15 of the compound reducing agent solution at a flow rate of 1.47 L / min, and then add the remaining silver ammonia solution and the compound reducing agent solution into the reactor at a flow rate of 1.47 L / min, heat to 50°C, react for 20 min, and obtain 1.6 micron spherical silver powder.

[0048] 3. Wash the spherical silver powder with water until the conductivity is 20 μs / cm, and then coat the surface of the washed spherical silver powder with hexadecanoic acid, wherein the mass ratio of hexadecanoic acid to the spherical silver powder is 0.003:1.

[0049] 4. Dry the coated spherical silver powder and spheroidize it for 5 minutes to obtain a solid density of 5.5g / cm 3 , bulk density is 3.32g / cm 3 Spherical silver powder, such as Figure 1 shown.

[0050] 5. Stir the spherical silver powder, oleic acid and alcohol for 10 minutes, add zirconium balls with a diameter of 1.4 mm, grind for 15 hours, filter, wash and dry to obtain 3.1 g / cm 3 High pine package silver flake powder, such as Figure 2 As shown, the mass ratio of oleic acid, zirconium balls, alcohol and spherical silver powder after spheroidization is 0.8:4.5:0.6:1.

[0051] Embodiment 2:

[0052] 1. Use silver nitrate to prepare a silver ammonia solution with a molar concentration of 1 mol / L.

[0053] Ascorbic acid and formaldehyde with a concentration of 37% were mixed in a mass ratio of 1:2 to prepare a composite reducing agent solution with a molar concentration of 0.5 mol / L.

[0054] Polyvinyl pyrrolidone K30 and gum arabic were mixed in a mass ratio of 4.5:1 to prepare a composite dispersant solution with a mass concentration of 25 g / L.

[0055] The volume ratio of the prepared silver ammonia solution to the compound reducing agent solution is 1: 1. The mass ratio of polyvinyl pyrrolidone K30 and gum arabic in the prepared compound dispersant solution to silver nitrate in the silver ammonia solution is 1: 6.8.

[0056] 2. Under stirring at a speed of 350 r / min, first add the prepared compound dispersant solution into the reaction vessel, then add 1 / 20 of the silver ammonia solution at a flow rate of 1.96 L / min, then add 1 / 20 of the compound reducing agent solution at a flow rate of 1.96 L / min, and then add the remaining silver ammonia solution and the compound reducing agent solution into the reactor at a flow rate of 1.96 L / min, heat to 45 ° C, react for 10 min, and obtain 2.5 micron spherical silver powder.

[0057] 3. Wash the spherical silver powder with water until the conductivity is 18 μs / cm, and then coat the surface of the washed spherical silver powder with stearic acid, wherein the mass ratio of stearic acid to spherical silver powder is 0.008:1.

[0058] 4. The surface-coated spherical silver powder was dried and spheroidized for 8 minutes to obtain a solid density of 5.7 g / cm 3 , bulk density is 3.42g / cm3 Spherical silver powder, such as Figure 3 shown.

[0059] 5. Stir the spherical silver powder, linolenic acid and alcohol for 8 minutes, add a steel ball with a diameter of 1.2 mm, grind for 18 hours, filter, wash and dry to obtain 3.28 g / cm 3 High pine package silver flake powder, such as Figure 4 As shown, the mass ratio of linolenic acid, steel balls, alcohol and spherical silver powder after spheroidization is 1.0:5.0:0.8:1.

[0060] Embodiment 3:

[0061] 1. Use silver nitrate to prepare a silver ammonia solution with a molar concentration of 1.5 mol / L.

[0062] Ascorbic acid and formaldehyde with a concentration of 37% were mixed in a mass ratio of 1:1.5 to prepare a composite reducing agent solution with a molar concentration of 1.5 mol / L.

[0063] Polyvinyl pyrrolidone K30 and gelatin were mixed in a mass ratio of 3.5:1 to prepare a composite dispersant solution with a mass concentration of 20 g / L.

[0064] The volume ratio of the prepared silver ammonia solution to the compound reducing agent solution is 1:1. The mass ratio of polyvinyl pyrrolidone K30 and gelatin in the prepared compound dispersant solution to silver nitrate in the silver ammonia solution is 1:12.7.

[0065] 2. Under stirring at a speed of 250 r / min, first add the prepared compound dispersant solution into the reaction vessel, then add 1 / 18 of the silver ammonia solution at a flow rate of 1.75 L / min, then add 1 / 18 of the compound reducing agent solution at a flow rate of 1.75 L / min, and then add the remaining silver ammonia solution and the compound reducing agent solution into the reactor at a flow rate of 1.75 L / min, heat to 48 ° C, react for 30 min, and obtain 2.0 micron spherical silver powder.

[0066] 3. Wash the spherical silver powder with water until the conductivity is 15 μs / cm, and then use lauric acid to coat the surface of the washed spherical silver powder, wherein the mass ratio of lauric acid to spherical silver powder is 0.002:1.

[0067] 4. The surface-coated spherical silver powder was dried and spheroidized for 3 minutes to obtain a solid density of 5.6 g / cm 3 , bulk density is 3.37g / cm 3 Spherical silver powder.

[0068] 5. Stir the spherical silver powder, linoleic acid and alcohol for 12 minutes, add a steel ball with a diameter of 1.6 mm, grind for 128 hours, filter, wash and dry to obtain 3.16 g / cm 3 The mass ratio of linoleic acid, steel ball, alcohol and spherical silver powder after spheroidization is 0.9:4.8:0.7:1.

[0069] The flaky silver powder of the above-mentioned Examples 1, 2 and 3 was fused with an organic carrier under an epoxy system, and the silver content was controlled to be about 40%. Then the prepared silver paste was rolled for 3 times. Finally, the rolled silver paste was screen-printed on a PET sheet, with a printing line width of 0.8 mm, a line length of 1 m, a drying temperature of 150°C, and a time of 50 minutes. The test line resistance was as follows: The D50 of the flaky silver powder of Examples 1, 2 and 3 was 2.1 microns, 3.1 microns and 2.7 microns, and the bulk density was 3.1 g / cm 3 、3.28g / cm 3 and 3.16 g / cm 3 The resistance values ​​are 75Ω, 70Ω and 72Ω respectively. The flaky silver powders of Examples 1, 2 and 3 have good compactness.

[0070] Please note that the technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above embodiments only express several implementation methods of the present application, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several variations and improvements can be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be based on the attached claims.

Claims

1. A method for preparing high-loose flaky silver powder, characterized in that: The preparation method comprises: Step S1, under stirring, adding a composite dispersant solution with a mass concentration of 15-25 g / L into a reaction container, then adding a silver ammonia solution with a molar concentration of 1-2 mol / L at a flow rate of 1.47-1.96 L / min, then adding a composite reducing agent solution with a molar concentration of 0.5-1.5 mol / L at the same flow rate, then adding the remaining silver ammonia solution and the composite reducing agent solution into the reactor at the same flow rate, heating to 45-50° C., reacting for 10-30 min, and obtaining spherical silver powder of 1.6-2.5 microns; In step S1, the volume ratio of the silver ammonia solution to the composite reducing agent solution is 1:1; In the step S1, the mass ratio of the compound dispersant in the compound dispersant solution to the silver nitrate in the silver ammonia solution is 1:6.8-23; Step S2, washing the spherical silver powder with water until the conductivity is ≦20 μs / cm, and then coating the surface of the washed spherical silver powder with saturated fatty acid; In the step S2, the mass ratio of the saturated fatty acid to the spherical silver powder is 0.002-0.008:1; Step S3, drying the surface-coated spherical silver powder and spheroidizing for 3 to 8 minutes; Step S4, stirring the spherical silver powder, unsaturated fatty acid grinding aid and alcohol for 8 to 12 minutes, adding grinding balls, grinding for 12 to 18 hours, filtering, washing and drying to obtain high loose flaky silver powder. In the step S4, the mass ratio of the unsaturated fatty acid grinding aid, grinding balls, alcohol and spherical silver powder after spheroidization is 0.8-1.0:4.5-5.0:0.6-0.8:

1.

2. The preparation method according to claim 1, characterized in that: In step S1, the volume ratio of the silver ammonia solution added first to the silver ammonia solution added later is 1:15-20; The volume ratio of the composite reducing agent solution added first to the composite reducing agent solution added later is 1:15-20.

3. The preparation method according to claim 2, characterized in that: In the step S1, the solute in the composite reducing agent solution is a mixture of ascorbic acid and formaldehyde with a concentration of 37%; In the step S1, the compound dispersant is a mixture of polyvinyl pyrrolidone K30 and gum arabic, or a mixture of polyvinyl pyrrolidone K30 and gelatin.

4. The preparation method according to claim 3, characterized in that: The mass ratio of ascorbic acid to formaldehyde is 1:1-2; The mass ratio of polyvinyl pyrrolidone K30 to gum arabic is 3.5-4.5:1; The mass ratio of the polyvinyl pyrrolidone K30 to gelatin is 3.5-4.5:

1.

5. The preparation method according to any one of claims 1 to 4, characterized in that: In the step S1, the stirring speed in the stirring state is 250-350 r / min.

6. The preparation method according to claim 5, characterized in that: In the step S2, the electrical conductivity is 15-18 μs / cm.

7. The preparation method according to claim 5, characterized in that: In the step S2, the saturated fatty acid is one of hexadecanoic acid, stearic acid, lauric acid and myristic acid.

8. The preparation method according to claim 7, characterized in that: In step S4, the diameter of the grinding balls is 1.2 to 1.6 mm; The grinding balls are steel balls or zirconium balls.

9. The preparation method according to claim 8, characterized in that: In step S4, the unsaturated fatty acid grinding aid is one of oleic acid, linolenic acid, linoleic acid, arachidonic acid and docosenoic acid.

10. A high loose package flaky silver powder, characterized in that: The takomatsu flaky silver powder is prepared by the method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Flaky silver powder with low apparent density and preparation method of flaky silver powder

    CN110026564A

  • Low-apparent flake silver powder and preparation method and application thereof

    CN118023512A

  • Silver powder, method for producing same, and conductive paste

    CN106573300A

  • Preparation method of high tap density and high-dispersion spherical silver powder

    CN110434355A

  • Preparation method and application of silver powder with high sintering activity

    CN115780824A